Potential use of low-NDGA Larrea divaricata extracts as antioxidant in foods - Turner, Sebastian Turner (2011)
Larrea divaricata Cav. is widely distributed in Argentina. Aqueous extract, of its leaves, has documented antitumoral and immunomodulatory activities. In this study, the antioxidant activity of aqueous extract and a component, nordihydroguaiaretic acid was determined and compared using different assays. Both the aqueous extract and nordihydroguaiaretic acid exhibited antioxidant activity. However, results show that it is very likely that compounds other than nordihydroguaiaretic acid could be involved in the antioxidant activity of the extract. Since nordihydroguaiaretic acid is nephrotoxic and hepatotoxic agent, it is important to direct efforts toward the potential use of low-nordihydroguaiaretic acid L. divaricata extracts as antioxidant in foods.